PEDAGOGICAL MODELS AND STRATEGIES FOR INTEGRATING TECHNICAL AND TRANSVERSAL COMPETENCIES IN HIGHER EDUCATION - Makhammatova, Hilola; Bakhtiyorova, Dilnoza (International Conference on Science, Education & Law, 2025)
This article examines the integration of technical and transversal competencies in higher education through modern pedagogical models and evidence-based instructional strategies. It analyses the role of competency-based education, project-based learning, CLIL, STEAM, and collaborative learning frameworks in shaping students’ communication, creativity, critical thinking, problem solving, and technical skills. Drawing on the works of Uzbek, CIS, and international scholars, the study highlights methods and exercises such as role-play, case-study analysis, design thinking cycles, peer collaboration tasks, engineering simulations, coding labs, and industry-based capstone projects that ensure the simultaneous development of both skill domains. Statistical findings from a quasi-experimental study demonstrate significant improvements in students’ professional and transversal competencies, confirming the effectiveness of integrated instructional design